Pemanfaatan Umbi Suweg (Amorphophallus sp) sebagai Bahan Baku Pembuatan Bioetanol melalui Proses Fermentasi dan Distilasi - Hargono H.; Adimas Wahyu Santoso; Gleys Kasih Deborah (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Suweg (Amorphophallus sp) is a plant that is easy to grow. Bulbs of this type is rarely used as food because the tuber contains compounds that cause itching. The carbohydrate content in tubers of 17.5%, so the bulbs suweg worthy of ethanol (bioethanol). The process used to convert starch into bioethanol suweg through enzymatic hydrolysis stages continued fermentation. The process of enzymatic hydrolysis using the enzyme α-amylase and gluco-amylase, while the fermentation process using the yeast Saccharomyces cerevisiae. As the growth of bacteria use nutrients NPK and urea. Substrate concentration of 20% (w / w), α-amylase enzyme dose and gluco-amylase : 1.0, 1.5 and 2% (w / w), respectively. The next best glucose results generated from the hydrolysis process is fermented using yeast mass of 20 g / L with a variety of nutrient mass of a mass of urea and NPK 3, 5, 7, and 11 g / L, .respectively.  Bioethanol fermentation results in the form of crude subsequently purified by distillation. Hydrolysis using each dosage α-amylase and gluco-amylase as much as 1.5% yield of glucose 11.9 g / L. In the fermentation process, the addition of nutrient effect on ethanol. The highest ethanol content of fermented mass produced by the addition of NPK nutrients in variable 5 g / L that is equal to 8.5%. Separation by distillation of the stage to produce ethanol 65%.